2022
DOI: 10.1111/jfbc.14387
|View full text |Cite
|
Sign up to set email alerts
|

Role of Medicinal plant‐derived Nutraceuticals as a potential target for the treatment of breast cancer

Abstract: Breast cancer (BC) is one of the most challenging cancers to treat, accounting for many cancer‐related deaths. Over some years, chemotherapy, hormone treatment, radiation, and surgeries have been used to treat cancer. Unfortunately, these treatment options are unsuccessful due to crucial adverse reactions and multidrug tolerance/resistance. Although it is clear that substances in the nutraceuticals category have a lot of anti‐cancer activity, using a supplementary therapy strategy, in this case, could be very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 112 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…As a result of the presence of different bioactive molecules in medicinal plants, their preparation as teas, hydroethanolic extracts, or supplements may be considered as an alternative therapeutic and nutraceutical approach [58][59][60]. Thus, the search for different antioxidant nutraceuticals, as medicinal plants, whose use can supplement phytochemical intake and promote human health, has intensified [61][62][63]. Moreover, the recently obtained scientific data have shown that continuous pharmacological screening of different plants extracts is still an important step towards the development of new natural products, phytotherapeutics, and nutraceuticals to be used for the prevention and treatment of diseases [64].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the presence of different bioactive molecules in medicinal plants, their preparation as teas, hydroethanolic extracts, or supplements may be considered as an alternative therapeutic and nutraceutical approach [58][59][60]. Thus, the search for different antioxidant nutraceuticals, as medicinal plants, whose use can supplement phytochemical intake and promote human health, has intensified [61][62][63]. Moreover, the recently obtained scientific data have shown that continuous pharmacological screening of different plants extracts is still an important step towards the development of new natural products, phytotherapeutics, and nutraceuticals to be used for the prevention and treatment of diseases [64].…”
Section: Discussionmentioning
confidence: 99%
“…These products can easily extract bioactive substances like prebiotics or antioxidant metabolites [ 45 ]. In the analysis of FW’s metabolomics profile, few studies have been conducted to produce vinegar and wine from pineapple pulp and peel characterized by GC-MS and ultra-high performance liquid chromatography (UHPLC) hyphenated with quadrupole-time-of-flight tandem mass spectrometry (UHPLC-QTOF-MS) [ 46 ], essential oils from plants in the genus Lavandula, mainly L. intermedia and L. angustifolia , functional foods and nutraceuticals from by-products of Vicia faba beans, and supplements with therapeutic uses from Passiflora mollissima seeds confirmed by using (UHPLC-QTOF-MS) [ 47 , 48 , 49 ]. Using a different technique, like nuclear magnetic resonance (NMR)-based metabolomics analysis revealed alterations in primary and secondary metabolites (e.g., amino acids, carbohydrates, and phenolics) in banana fruits during postharvest senescence [ 50 ].…”
Section: Food Waste Managementmentioning
confidence: 99%
“…One of the best ways to combat cancer, including breast cancer, among the various therapeutic options currently accessible, is to use chemical formulations or chemicals derived from natural sources. Currently on the market, almost 60 % of cancer medications come from natural sources ( Alharbi et al, 2022 ). Phytochemicals have few side effects and a high cancer effectiveness.…”
Section: Introductionmentioning
confidence: 99%